Business Plan : SweetLicious Bakery / Adam Izzat Azmi…[et al.] - Azmi, Adam Izzat; Rosli, Aidil Aiman; Baharom, Nur Alya Tasneem; Yahaya, Nurul Izatil Syamimi; Zaidi, Siti Nur Izzati (2021)
Sweetlicious Bakery will be specializing in visually attractive cakes, breads, and cookies. There has been a significant increase in demand for tasteful, overindulgent, and visually stimulating cakes. Sweetlicious Bakery is a form of business based on partnership which consist of five members which hold important position such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. This bakery has various types of delicious and interesting cakes, breads, and cookies for customers to enjoy. Sweetlicious Bakery with motto of ‘So Sweet. So Good. Sure to bring smiles’ is located at Jalan Jambatan Sultan Yahaya Petra, Kampung Sirih, 15150 Kota Bharu, Kelantan, Malaysia. Sweetlicious Bakery is a bakery which focuses on production of the premier company in the baking industry and the related food and beverage industry, known and emulated for our best quality products that delight the consumer in Malaysia. Delicious Bakery aims to be a cornerstone in the community creating a neighbourhood atmosphere where customers feel comfortable and become instant regulars. We seek fair and responsible profit, enough to keep the company financially healthy for the long term and to fairly compensate owners and investors for their money and risk. To make it more attractive we decided to make some innovation by implying our creativity and modern element in the cakes, breads, and cookies. We have done some research that Malaysia loves something beautiful and interesting so it makes it viral and become a phenomenon in the country. Thus, we recommended this bakery because it suitable with all type of income level as the prices of our cakes, breads and cookies is affordable and worth it.